Review of the handbook Understanding Organisational Culture - Greco, Francesca (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Antonio Cocozza’s essay ‘Understanding Organisational Culture: Innovation, Transparency, Leadership, Community’ is characterised by the centrality the text attributes to culture as the key to interpreting organisational phenomena. It is the result of many years of study, research, teaching and action in the field, from the corporate world, to public administration, and in other contexts, such as organisations and representative associations. The handbook is aimed at those who wish to address the evolution of organisational studies in a systematic way, examining the polysemic concept of organisation and the new interpretative paradigms, in relation to the profound economic and social changes taking place in recent decades. The reflection proposed by the author goes beyond the traditional approach to the study of organisations, generally of a structuralist and functionalist type, in an interdisciplinary perspective that aims to investigate both the role played by cultures and the ethical, symbolic and value dimensions in the dynamics of redefining strategic assets and in the search for new governance in innovative organisations.